Development and Validation of a New Measure of Intuition: The Types of Intuition Scale1. (16th May 2014) - Pretz, Jean E.; Brookings, Jeffrey B.; Carlson, Lauren A.; Humbert, Tamera Keiter; Roy, Michael; Jones, Meghan; Memmert, Daniel
ABSTRACT The Types of Intuition Scale (TIntS) measures three types of intuition identified in a literature review by Pretz and Totz (2007): holistic, inferential, and affective. Holistic intuitions integrate diverse sources of information in a Gestalt‐like, non‐analytical manner; inferential intuitions are based on previously analytical processes that have become automatic; and affective intuitions are based on feelings. Current intuition measures inadequately assess these distinct types. We report four validity studies: Study 1 reports the reliability and factor structure of the TIntS and correlations with extant intuition and personality measures. Study 2 presents a confirmatory factor analysis. Studies 3 and 4 examine the predictive validity of the TIntS with respect to clinical decision making in occupational therapy and musical performance. Scales were internally consistent and stable over time, and factor analyses supported the predicted distinctions among them. Correlations with existing measures of intuition, personality, and behavior showed that the TIntS is unique in its assessment of all three types of intuition in one measure. Copyright © 2014 John Wiley & Sons, Ltd.